Investigation of the novel mTOR inhibitor AZD2014 in neuronal ischemia. (27th July 2019) - Hadley, Gina; Beard, Daniel J.; Alexopoulou, Zoi; Sutherland, Brad A.; Buchan, Alastair M.
Highlights: Inhibiting mTOR via hamartin is endogenously neuroprotective through productive autophagy. AZD2014, a dual mTORC1/2 inhibitor is detrimental to ischemic neurons. AZD2014 reduces hamartin expression preventing neuroprotective effects. The mechanism for endogenous neuroprotection may relate to the differential effects of mTORC1 and mTORC2. Abstract: Introduction: Hamartin, a component of the tuberous sclerosis complex (TSC) that actively inhibits the mammalian target of rapamycin (mTOR), may mediate the endogenous resistance of Cornu Ammonis 3 (CA3) hippocampal neurons following global cerebral ischemia. Pharmacological compounds that selectively inhibit mTOR may afford neuroprotection following ischemic stroke. We hypothesize that AZD2014, a novel mTORC1/2 inhibitor, may protect neurons following oxygen and glucose deprivation (OGD). Methods: Primary neuronal cultures from E18 Wistar rat embryos were exposed to 2 h OGD or normoxia. AZD2014 was administered either during OGD, 24 h prior to OGD or for 24 h following OGD. Cell death was quantified by lactate dehydrogenase assay. We characterized the expression of mTOR pathway proteins following exposure to AZD2014 using western blotting. Results: Following 2 h OGD +24 h recovery, AZD2014 increased neuronal death when present during OGD. Rapamycin, the archetypal mTOR inhibitor, had no effect on cell death. Treatment with AZD2014 24 h prior to OGD and 24 h after OGD also enhanced cell death. While Western blotting showed a trend towards decreased expression levels of phospho-Akt relative to total Akt with increasing AZD2014 concentration, hamartin expression was also significantly decreased leading to activation of mTOR. Conclusion: AZD2014 was detrimental to neurons that underwent ischemia. AZD2014 appeared to reduce hamartin, a known neuroprotective mediator, thereby preventing any beneficial effects of mTOR inhibition. Further characterization of the role of individual mTOR complexes (mTORC1 and mTORC2) and their upstream and downstream regulators are necessary to reveal whether these pathways are neuroprotective targets for stroke.